Decreased FGF19 and FGF21: possible underlying common pathogenic mechanism of metabolic and cognitive dysregulation in depression - Tang, Mimi; Cheng, Shuqiao; Wang, Lu; Tang, Hui; Liu, Ting; Zhao, Tingyu; Dang, Ruili (Frontiers in Neuroscience, 2023)
Background: Accumulating studies suggested that major depressive disorder (MDD) was closely related to metabolic syndrome (MetS). Fibroblast growth factors (FGFs) 15/19 and 21, important endogenous regulators were also reported to participate in psychiatric disorders. This study aimed to investigate the role of FGF19 and FGF21 in MDD and to explore possible pathogenic mechanism of metabolic and cognitive dysregulation in depression. Methods: A total of 59 MDD patients and 55 healthy control participants were recruited. The serum levels of FGF19, FGF21 and lipid profiles were measured by means of enzymatic methods. Cognitive function was measured by repeatable battery for the assessment of neuropsychological status (RBANS) scores. The gene expression of PGC-1α and FNDC5 was determined by quantitative polymerase chain reaction (PCR). Results: We found that plasma FGF19 and FGF21 levels were significantly decreased in patients with MDD. Meanwhile, correlation analyses showed associations between FGF19/FGF21 levels and metabolic and cognitive dysregulation in depression. Additionally, FGF19/FGF21 levels were also associated with gene expression of PGC-1α and FNDC5. Conclusions: This study elucidated the role of FGF19 and FGF21 in MDD. Metabolic and cognitive dysregulation in MDD patients had been evaluated and linked to the decreased concentrations of FGF19 and FGF21 through PGC-1α/FNDC5 pathway. Our results showed the alterations of FGF19 and FGF21 levels may be a common pathogenic mechanism of the metabolic and cognitive disturbances in patients with MDD.